Formação do leitor e as obras indicadas para os vestibulares - Quadros, Tiane Reusch de (2007)
Considering the proposals of LDB for the High School, this study proposes a reflection about the work with the subject matter of Brazilian Literature, specifically refering to the books indicated to the entrance selective processes of the Federal University of Santa Maria (PEIES and vestibular). The existence of entrance exams to access the College is a decisive factor in the definition of the contents that have been taught in High Schools because lots of students intend to take such exams. This research checks whether the entrance exams and other entrance selective processes like PEIES are barriers in the teaching of Brazilian Literature. It also searches for ways of working with the books indicated to the entrance exams without compromising other contents and goals of the subject matter. It was also observed whether teachers were willing to correlate the books used in Brazilian Literature with the current society s context, because we believe this can be a way to motivate students to think critically about the world around them. The beginning of chapter one consists of an analysis of fragments of an interview made with Brazilian Literature teachers who work with third grade of High School in Santa Maria city. The goal is to identify how they deal with the work with the subject and with literary books. Two public schools, one private and one technical school associated to UFSM were chosen to be part of this research. A questionnaire was also used to check the way students relate themselves with studies of Brazilian Literature and with the books indicated to PEIES and UFSM college entrance exam. The second part of this research is made up by the analysis of two literary books called Terras do sem-fim and Contos gauchescos. The focus is on significant points of those books, which could be taken as starting points for an approach between the literary book and the student s reality. The interpretation study proposed in the paper is presented in contrast to the interview made with teachers about their work with those literary books. In the third chapter some points covered through out the research are revisited in order to get a qualification of the Brazilian Literature teaching in High School. Only with a constant revaluation of the teaching practices it will be possible to achieve improvements in the formation of readers and of people who like literary works